1996
DOI: 10.1002/ana.410390119
|View full text |Cite
|
Sign up to set email alerts
|

SOD1 mutation is assosiated with accumulation of neurofilaments in amyotrophic lateral scelaries

Abstract: Mutations in the Cu/Zn superoxide dismutase (SOD1) gene are found in 15 to 20% of patients with familial amyotrophic lateral sclerosis (FALS). Increased levels of neurofilament subunits in transgenic mouse models of ALS also suggests a key role for these proteins in the pathogenesis of the disease. We report the coexistence of an Ile113-->Thr substitution in exon 4 of the SOD1 gene and marked neurofilamentous pathology in the same FALS patient. These observations suggest that two mechanisms, SOD1-induced toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
107
0
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(115 citation statements)
references
References 16 publications
7
107
0
1
Order By: Relevance
“…122 Higher expression levels of the same construct with the mouse Thy1.2 promoter (ALZ17 line) also failed to develop NFT or cell loss despite extensive phosphorylation of tau and axonal pathology in central and spinal cord neurons [123][124][125] similar to that seen in spinal cord motor neurons of people with amyotrophic lateral sclerosis. 126 Consistent with the observation of axonopathy, behavioral studies of these mice showed muscle weakness. 124 These two models showed that overexpression of human wild-type 4 repeat tau is insufficient to induce NFT formation, but the somatodendritic localization of tau in neurons does resemble the "pre-tangle" state observed in AD.…”
Section: Tau Transgenic Mouse Modelssupporting
confidence: 78%
“…122 Higher expression levels of the same construct with the mouse Thy1.2 promoter (ALZ17 line) also failed to develop NFT or cell loss despite extensive phosphorylation of tau and axonal pathology in central and spinal cord neurons [123][124][125] similar to that seen in spinal cord motor neurons of people with amyotrophic lateral sclerosis. 126 Consistent with the observation of axonopathy, behavioral studies of these mice showed muscle weakness. 124 These two models showed that overexpression of human wild-type 4 repeat tau is insufficient to induce NFT formation, but the somatodendritic localization of tau in neurons does resemble the "pre-tangle" state observed in AD.…”
Section: Tau Transgenic Mouse Modelssupporting
confidence: 78%
“…However, these additional lines of transgenic mice did not develop prominent NF-rich inclusions in spinal cord motor neurons like the G1H mice. Since another report that appeared after the submission of our paper confirms the presence of NF-rich lesions in the spinal cord of a human patient with FALS due to an I113T SOD1 mutation (51), the neuropathology of authentic FALS in humans and in transgenic mice that express mutant human SOD1 may depend upon the specific mutation in the SOD1 gene.…”
mentioning
confidence: 54%
“…Aberrant accumulation of pNF in axonal swellings and somas has been a hallmark of axonal transport disruption in neurodegenerative diseases (Manetto et al, 1988;Munoz et al, 1988;Mizusawa et al, 1989;Sobue et al, 1990;Rouleau et al, 1996;Stokin et al, 2005). Because phosphorylation of neurofilaments has been shown to de- crease active transport of neurofilaments through retinal axons (Jung and Shea, 1999), it is possible that excess pNF within intraocular axons may itself cause progressive declines in RGC gene expression and retrograde transport.…”
Section: Discussionmentioning
confidence: 99%